Pengembangan Bahan Ajar Fisika Dasar Terintegrasi Nilai Islam dalam Meningkatkan Kemampuan Literasi Sains - Kadir, Abdul (Institut Agama Islam Negeri Kendari, 2023)
This R & D research aims to develop basic physics teaching materials integrated with Islamic values in improving scientific literacy skills. Data was obtained from validation sheets and product implementation observations, student response questionnaires to products, and valid and reliable scientific literacy ability tests. The data analysis technique uses descriptive and inferential analysis after fulfilling the normality and homogeneity test requirements. The results of the validity test of basic physics teaching materials integrated with Islamic values have an average value of 94.26% with validity criteria categorized as very valid. The results of the product practicality test have an average value of 1.64, meaning that it has met the practicality criteria in the implemented category. The results of the product effectiveness test have an average value of student responses to teaching materials of 3.54 or 82.26% with a very positive response category, so that the teaching materials used have a good effect in increasing students' scientific literacy. This research indicates that basic physics teaching materials that are integrated with Islamic values are suitable for use as learning resources because they meet the criteria of being valid, practical and effective.Keywords: Basic physics; development; Islamic values; science literacy ability; teaching materials